Social Perception of Watershed Degradation and Its Influence on Collective Conservation Behavior - Asikin Muchtar (Jurnal Ragam Pengabdian, 2026)
The Rongkong Watershed (DAS) in North Luwu Regency is a strategic area in flash flood control, but it also represents a space of ecological and social trauma after the 2020 flash flood event. Until now, the management of the Rongkong watershed has tended to be dominated by technical and structural approaches, such as the construction of dams, hydrological monitoring stations, and the reforestation of critical land, while the social dimension of community perception and collective conservation behavior has not been the main focus. This study aims to analyze the social perception of the community towards the degradation of the Rongkong watershed and its influence on the formation of collective conservation behavior after the disaster. The study used a qualitative approach with a case study design, involving 12 key informants who were purposively selected from the upstream, middle, and downstream watersheds. Data were collected through in-depth interviews, field observations, and documentation, then analyzed using thematic analysis. The results show that the direct experience of flash floods shapes diverse social perceptions, ranging from reflective perceptions that view watershed degradation as a shared ecological threat to passive perceptions that place disasters as external phenomena. Reflective perceptions tend to encourage community participation in collective conservation activities, such as reforestation and environmental mutual cooperation, while passive perceptions underscore social engagement and reliance on structural interventions. This study concludes that the effectiveness of watershed management is not only determined by technical solutions, but is greatly influenced by how communities interpret watershed degradation and its social role in conservation efforts, so that the integration of social perception dimensions is key in community-based sustainable watershed management.